Parkinsonia glauca (Caesalpinioideae, Leguminosae), a new combination and status - Romão, Marcos Vinicius Varjão; Mansano, Vidal De Freitas (Phytotaxa, 2020)
A phylogenetic study with chloroplast molecular data for the trnL-F, rbcL and rps16 regions from Peltophorum group (Haston et al. 2005) indicated that Parkinsonia Linnaeus (1753: 375) and Cercidium Tulasne (1844: 133) are paraphyletic when recognized as distinct genera (Sargent 1889, Johnston 1924, Carter 1974) and form a well-sustained monophyletic group when considered together. Thus, the phylogenetic topology encouraged Haston et al. (2005) and Felger et al. (2017) to consider Cercidium as synonym of Parkinsonia, which has priority over the former name.